Demonic Influence: The Negative Mental Health Effects of Belief in Demons - Nie, Fanhao (Journal for the scientific study of religion, 2016)
Many religious traditions include a belief in the reality of demonic beings and evil powers. Previous research demonstrates that comforting beliefs, such as believing in an afterlife, can benefit mental health, but less is known about the potentially negative mental health effects of belief in evil supernatural powers. In cross-sectional analyses, we find that among young adults, believing in demons is one of the strongest (negative) predictors of mental health. More importantly, using three waves of the National Study of Youth and Religion and a cross-lagged structural equation model, we find that belief in demons can lead to lowered mental health in later waves but low mental health does not lead to greater belief in demons. In fact, when predicting changes in mental health from wave 2 to wave 3 of the study, the negative effect size of belief in demons on mental health is larger in magnitude than all other religion-related predictors.